Brentuximab vedotin for recurrent Hodgkin lymphoma after allogeneic hematopoietic stem cell transplantation: a report from the EBMT Lymphoma Working Party - Bazarbachi, Ali; Dreger, Peter (Cancer, 2018)
Background The treatment of patients with Hodgkin lymphoma (HL) who develop disease progression after undergoing allogeneic stem cell transplantation (allo-SCT) remains challenging. Methods The authors assessed outcomes in 184 adult patients with HL who developed disease recurrence or progression after a matched related or unrelated allo-SCT at European Society for Blood and Marrow Transplantation-participating centers between 2010 and 2014. Results Eighty patients who received brentuximab vedotin (BV) salvage therapy were compared with 104 patients who did not. Patients in the BV group were younger (median age of 30 years vs 34 years) and were more likely to receive pretransplant BV (65% vs 46%) or posttransplant donor lymphocyte infusion (66% vs 33%). The 2 groups otherwise were comparable. Patients in the BV group received a median of 6 doses of posttransplant BV, resulting in a complete remission rate of 29%, a partial response rate of 45%, and a stable disease rate of 26%. Response to BV after allo-SCT did not appear to be affected by receipt of pretransplant BV. Despite a longer median follow-up for surviving patients in the BV group (33 months vs 23 months; P<.001), approximately 34% of the original BV cohort were alive and in CR at the time of last follow-up versus 18% in the group that did not receive BV (P=.003). The use of BV before donor lymphocyte infusion was found to be associated with the highest probability of being alive and in CR (40%) at the time of last follow-up. Salvage BV appeared to have no effect on chronic graft-versus-host disease or 1-year overall survival from the time of disease recurrence after allo-SCT (76% vs 67%). Conclusions BV is a safe and effective salvage therapy for patients with HL who develop disease recurrence or progression after undergoing allo-SCT, even after prior exposure to BV.
Published online October 23, 2018
Gesehen am 03.07.2019